Contaminants on Electrical Contacts Used in Semiconductor Device Testing - SAID, MD RADZAI; Tan, CheeFai (IDOSI Publications, 2013)
Electrical contacts used in semiconductor device testing are often deposited with a small pip of dark colour contaminants after being subjected to repeating cycles of impact loading. Samples of used electrical contacts are checked under SEM and EDX. It is discovered that the contaminants contain high percentage of tin elements. The reason as to why the contamination formed is investigated and it is found to be the result of material transfer from device lead. It is caused by the molten metal bridge formed when the contact begins to move apart.